Building Eating Skills in Primary School Student Through Micro Curriculum Development Using Understanding by Design (UbD) - Zhahira, Bilqis Syazqya; Cahya, Lusi Nur; Mulyasari, Effy (International Conference on Elementary Education, 2025)
Based on observations and interviews with teachers in primary schools in Bandung, many students still need help with self-reliance, especially in eating skills. This is important because it will be a provision for students as they become adults and depend on their own abilities. To have good self-reliance, it is also necessary to have good planning. Through Understanding by Design (UbD), three stages need to be done: 1) identification of the desired results, 2) determining evidence of assessment, and 3) planning learning instruction. This research aims to develop a micro curriculum for building primary students’ self-reliance on eating skills seen from the UbD framework. The research method used is Design and Development or DnD, which was adopted by Richey and Klein, with the Planning, Production, and Evaluation Model (PPE). The participants in this study called experts to evaluate the feasibility of a micro curriculum of eating skills, among others, of teaching materials, language learning, learning media, and learning instruction. The instruments used were a set of questionnaires using Likert Scales, and the result was processed in qualitative data. The data analysis showed that the feasibility of a material expert score was 98, referring to excellent categories; 82,5 from a language expert, referring to good categories; 91 of a media expert, referring to excellent categories; and 100% of a learning instruction expert, referring to excellent categories. So, the average feasibility score from the experts is 93, which refers to excellent categories. Therefore, implementing this UbD micro curriculum to develop students’ eating skills at the primary school level is highly recommended.